2021
DOI: 10.1200/jco.20.02923
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab in Patients With Metastatic Breast Cancer With High Tumor Mutational Burden: Results From the Targeted Agent and Profiling Utilization Registry (TAPUR) Study

Abstract: PURPOSE The TAPUR Study is a phase II basket trial that aims to identify signals of antitumor activity of commercially available targeted agents in patients with advanced cancers harboring genomic alterations known to be drug targets. Results in a cohort of patients with metastatic breast cancer (mBC) with high tumor mutational burden (HTMB) treated with pembrolizumab are reported. METHODS Patients with advanced mBC received standard doses of either 2 mg/kg or 200 mg infusions of pembrolizumab every 3 weeks. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 31 publications
4
95
0
Order By: Relevance
“…Currently, three biomarkers have been clinically validated as predictors of response to immune checkpoint blockade in TNBC [i.e., PD-L1 (2)] and across cancer types (i.e., TMB (3,14) and mismatch repair deficiency (15). Indeed, the immunotherapy drug pembrolizumab for the treatment of patients with TMB-high tumors is approved by the Food and Drug Administration (FDA) (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, three biomarkers have been clinically validated as predictors of response to immune checkpoint blockade in TNBC [i.e., PD-L1 (2)] and across cancer types (i.e., TMB (3,14) and mismatch repair deficiency (15). Indeed, the immunotherapy drug pembrolizumab for the treatment of patients with TMB-high tumors is approved by the Food and Drug Administration (FDA) (14).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, immunotherapy with atezolizumab, an anti-PD-L1 drug antibody, has been approved for PD-L1-positive (PD-L1+) (i.e., ≥1% PD-L1+ tumor-infiltrating immune cells) advanced TNBC in combination with nab-paclitaxel (2). On the other side, activity of pembrolizumab monotherapy in patients with pretreated metastatic breast cancer with high TMB has recently been reported (3). However, no activity of immune checkpoint inhibitors in PD-L1-negative TNBC has been observed to date, and the predictive value of TMB beyond PD-L1 expression is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Standardization of detection assays is another challenge of precisely guiding the prescription of immunotherapy. Studies have shown that high tumor mutation burden (TMB) can predict the efficacy of breast cancer immunotherapy ( 76 , 77 ), but there is no uniform standard for TMB threshold. Although there are some discoveries in biomarker exploration currently, and PD-L1 is recognized, it is still insufficient for tumor microenvironment and biomarker research.…”
Section: Predictive Biomarkers Of Efficacymentioning
confidence: 99%
“…This trend was interestingly most notable in the ER+ subtype [ 18 ]. In contrast, the TAPUR trial included 28 breast cancer patients with high TMB (≥9 mutations per megabase) and showed an objective response rate of 21%, but subgroup analysis did not demonstrate that high TMB was a positive prognostic biomarker for treatment with ICIs [ 19 ]. Notably, the study was not powered to detect an association between TMB and progression-free survival (PFS).…”
Section: Tumor Cell Microenvironment Biomarkersmentioning
confidence: 99%